The Confidential Approach To The Work Of International Committee Of The Red Cross - دندش, دينا (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Under the four Geneva Conventions, the ICRC has received special privileges that no other humanitarian organization has received to enable it to carry out its humanitarian activity on the battlefield, after the ICRC, through its fieldwork in the years prior to these agreements, has demonstrated its merit in carrying out neutral humanitarian work, moving away from prejudice and striving to alleviate the suffering of those affected by the effects of war. Confidentiality in the ICRC's work does not mean condoning violations committed during armed conflicts, but rather trying to stop them in a different and more rational manner. Taking into consideration the importance of the ICRC's tasks, international courts have been granted the right not to testify to ensure that ICRC staff are kept confidential, as have the ICRC's headquarters agreements and many states.This approach has been a cause of differences of opinion between supporters and opponents of the secrecy approach, which has led us to highlight this approach and the main motives that make the ICRC follow it in performing its humanitarian tasks.